A bench-scale evaluation of different treatment options to produce bio-stable drinking water. Issue 4 (1st July 2003) - Barbeau, Benoît; Prévost, Michèle; Servais, Pierre; Laurent, Patrick
Abstract : Owing to increasingly stringent water quality regulations and concerns about emerging pathogens, many drinking water utilities are having to modify their treatment lines. Bench-scale evaluation can be a useful means for carrying out a preliminary assessment of treatment modifications under consideration. An example of such an evaluation, performed as an initial screening of treatment options for a big North American utility, is presented here. Four sampling campaigns aimed at investigating at a bench-scale the impact of different treatments (coagulation-flocculation-settling, moderate ozonation, and filtration; high dosage ozonation; chlorination followed by dechlorination) on water quality were performed in this study. Testing involved measurement of water quality parameters (turbidity, dissolved organic carbon, ultraviolet absorbance, specific ultraviolet absorbance) with special attention paid to parameters driving regrowth potential (biodegradable dissolved organic carbon (BDOC) and bacterial abundances). Main results show that ozonation always increases BDOC levels. "Full treatment" (coagulation-flocculation-settling, moderate ozonation, filtration) would not change the regrowth potential of the raw water drastically. A high dosage ozonation ("high O3 " scenario) could result in a substantial seasonal increase in BDOC concentrations. It would be logical to follow up this conclusion with a consideration of whether or not the higher bacterial regrowth that would take place in the distribution system, and due to these increases in BDOC concentration, could be controlled by maintaining oxidant residuals during distribution.